THE EFFECTIVENESS OF USING SPEECHACE IN IMPROVING THE VOCABULARY OF THE STUDENTS AT THE LANGUAGE CENTER UNIT - Riandini, Dini; Romadhoni, Nova Salma; Rofiqoh, Dayana (Language and Education Journal, 2025)
An important component in learning languages, especially English, is developing vocabulary skills. However, students experience difficulties in understanding vocabulary. The problems they face include a lack of vocabulary and audio speed. The problem of vocabulary skills in students can be overcome with the help of the Speechace application. This study aims to determine whether there is a significant difference in vocabulary mastery skills between students who received instruction using the Speechace application and those who did not. This study was conducted using a quasi-experimental method. To analyze the data, a t-test was used. Based on the results of the independent sample t-test, it was revealed that the pvalue (0.000) was smaller than the αvalue (0.05) and the t-value obtained (8.463) was greater than the t-table value (4.734). This indicates that students who received instruction using the Speechace application and those who did not have significantly different vocabulary mastery skills. Therefore, students can learn vocabulary more effectively by using the Speechace application as a learning aid, particularly for English.